Membangkitkan Semangat Belajar Siswa Sekolah Dasar Melalui Ekspansi Video Pembelajaran - Aisyah Harianto; Atiqah Zhafirah; Siti Aminah; Siti Luthfiyyah; Wismanto Wismanto (Lembaga Pengembangan Kinerja Dosen, 2024)
The world of education, especially in terms of learning media, is influenced by current technological developments. With the development of technology, we should be able to use it to solve problems, especially in the field of education. The use of video media as a learning tool in the classroom is one example of technology used in the world of education. With the aim of arousing elementary school students' enthusiasm for learning through the expansion of learning videos. This research uses a qualitative approach, involving content analysis techniques. The use of video as a learning medium is a data source for this analysis. Data collection techniques include analysis of data sources from national and international journals over the last five years. Several findings from the use of video media show that they can have a positive impact on learning activities, one of which is that they can make learning in class more fun and prevent students from getting bored. Students will achieve better learning outcomes if they have greater motivation to learn. Therefore, it can be concluded that the development of video-based learning media can be used effectively during the learning process.